Comparing diazonium modified and unmodified activated carbon cloths for energy storage in supercapacitors - Arnold Subrata; Richard D. Webster (Electrochemical Science Advances, 2022)
Abstract Activated carbon cloths (ACCs) were chemically modified with anthraquinone (AQ) groups and the resulting AQ‐modified ACCs were characterized and tested for their potential use in supercapacitors. At modest scan rates and current densities, AQ‐modified ACCs were found to store and release less charge than unmodified ACCs, under conditions where equivalent series resistance (ESR) is not minimized.